Electrochemistry-coupled to liquid chromatography-mass spectrometry-density functional theory as a new tool to mimic the environmental degradation of selected phenylurea herbicides. Issue 10 (1st October 2021) - Tonleu Temgoua, Ranil Clément; Bussy, Ugo; Alvarez-Dorta, Dimitri; Galland, Nicolas; Njanja, Evangeline; Hémez, Julie; Thobie-Gautier, Christine; Tonlé, Ignas Kenfack; Boujtita, Mohammed
Abstract : In vitro and in vivo experimental models, mainly based on cell cultures, animals, healthy humans and clinical trials, are useful approaches for identifying the main metabolic pathways. Abstract : In vitro and in vivo experimental models, mainly based on cell cultures, animals, healthy humans and clinical trials, are useful approaches for identifying the main metabolic pathways. However, time, cost, and matrix complexity often hinder the success of these methods. In this study, we propose an alternative non-enzymatic method, using electrochemistry (EC) coupled to liquid chromatography (LC) – high resolution mass spectrometry (HRMS) – DFT theoretical calculations (EC/LC-MS/DFT) for the mimicry/simulation of the environmental degradation of phenylurea herbicides, and for the mechanism elucidation of this class of herbicides. Fenuron, monuron, isoproturon, linuron, monolinuron, metoxuron and chlortoluron were selected as relevant model compounds. The intended compounds are oxidized by EC, separated by LC and detected using electrospray ionization HRMS. The main oxidation products were hydroxylated compounds obtained by substitution and addition reactions. Unstable quinone imines/methines, rarely observed by conventional methods, have been identified during the oxidative degradation of phenylurea herbicides for the first time in this study. Some were directly observed and the others were trapped by glutathione GSH. Reactions such as hydrolytic substitutions (−Cl/+OH and −C3 H7 /+OH and −CH3 /+OH and −OCH3 /+OH), aromatic hydroxylation, alkyl carbon hydroxylation, dehydrochlorination/dehydromethylation/dehydromethoxylation and conjugation have been successfully mimicked. The obtained results, supported by theoretical calculations, are useful for simulating/understanding and predicting the oxidative degradation pathways of pesticides in the environment.